Injection of synthetic mesenchymal stem cell mitigates osteoporosis in rats after ovariectomy. Issue 8 (16th May 2018) - Shen, Miaoda; Wu, Ronghuan; Jin, Rilong; Pan, Jun; Guo, Fang; Li, Zhuoyang; Lin, Xiangjin; Xu, Sanzhong
Abstract: Osteoporosis is a severe skeletal disorder. Patients have a low bone mineral density and bone structural deterioration. Mounting lines of evidence suggest that inappropriate apoptosis of osteoblasts/osteocytes leads to maladaptive bone remodelling in osteoporosis. It has been suggested that transplantation of stem cells, including mesenchymal stem cells, may alter the trajectory of bone remoulding and mitigate osteoporosis in animal models. However, stem cells needed to be carefully stored and characterized before usage. In addition, there is great batch‐to‐batch variation in stem cell production. Here, we fabricated therapeutic polymer microparticles from the secretome and membranes of mesenchymal stem cells (MSCs). These synthetic MSCs contain growth factors secreted by MSCs. In addition, these particles display MSC surface molecules. In vitro, co‐culture with synthetic MSCs increases the viability of osteoblast cells. In a rat model of ovariectomy‐induced osteoporosis, injection of synthetic MSCs mitigated osteoporosis by reducing cell apoptosis and systemic inflammation, but increasing osteoblast numbers. Synthetic MSC offers a promising therapy to manage osteoporosis.